A Test for the Mean in the Zero-Inflated Poisson Distribution - Ahmad Kamal, Nik; A.H, Pooi (Malaysian Journal of Science, 2007)
In analyzing Poisson-count data, sometimes a lot of zeros are observed. When there are too many zeros, a zero-inflated Poisson distribution can be a more suitable model to use. A test for the mean in the imperfect state can be obtained by using the conditional maximum likelihood estimator of and the asymptotic variance of . For moderately small sample size, the probability of the rejection region under the null hypothesis is found to have only a small variation around the targeted value as the value of the nuisance parameter varies.